2006
DOI: 10.1111/j.1574-6968.2006.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory components at thecsgDpromoter – additional roles for OmpR and integration host factor and role of the 5′ untranslated region

Abstract: CsgD is a master regulator of multicellular behaviour in Salmonella enterica serovar Typhimurium. Expression of CsgD is highly regulated on the transcriptional level. A nucleo-protein complex had been defined where the global regulators OmpR and integration host factor (IHF) bind up- and downstream of the csgD core promoter. In this study, the nucleo-protein complex of PcsgD was extended through characterization of additional OmpR and IHF binding sites that influence the transcriptional activity of the csgD pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…IHF has been indicated to be involved in regulation of the csgD promoter (Gerstel et al, 2003(Gerstel et al, , 2006. In fact, we identified two IHF-binding sites, one between 2188 and 2159 (IHF-1) and another between 296 and 237 (IHF-2), on the csgD promoter ( Fig.…”
Section: Transcription-factor-binding Sequences On the Csgd Promotermentioning
confidence: 81%
“…IHF has been indicated to be involved in regulation of the csgD promoter (Gerstel et al, 2003(Gerstel et al, , 2006. In fact, we identified two IHF-binding sites, one between 2188 and 2159 (IHF-1) and another between 296 and 237 (IHF-2), on the csgD promoter ( Fig.…”
Section: Transcription-factor-binding Sequences On the Csgd Promotermentioning
confidence: 81%
“…OmpR is part of the EnvZ (membrane bound sensor kinase)/OmpR two-component regulatory system able to change the OmpR phosphorylation pattern in response to environmental changes such as osmolarity (high osmolarity leads to high levels of phosphorylated OmpR (OmpR-P)) and pH. Several OmpR binding sites (D1-D7) in the cgsD promoter were identified using a combination of response genetic studies and in vitro experiments (gel shifts and DNase I footprints) (Gerstel, Kolb, & Römling, 2006;Gerstel, Park, & Römling, 2003), showing similarities to the well-characterized ompF promoter (Huang & Igo, 1996). Further experiments showed that high affinity binding of OmpR-P to D1, directly upstream of the −35 box, is sufficient for transcriptional activation, while binding to the adjacent D2 and D3-D6 boxes, located further upstream, represses transcription.…”
Section: Complex Regulation Of Csgd Expression By Trans (Ompr Ihf Hmentioning
confidence: 99%
“…1) (14,15,23,34). An unusually large region upstream and downstream of the csgD promoter has been implicated in the control of csgD expression through binding of several regulatory proteins (3,12,13,22); however, single point mutations in the csgD promoter region can lead to enhanced semiconstitutive and temperatureindependent expression of CsgD, which does not require the stress sigma factor RpoS (38). Many of the links between environmental cues and CsgD expression are still unclear and are likely to involve both transcriptional and posttranscriptional control.…”
mentioning
confidence: 99%